Pengaruh Komunikasi Efektif Dalam Human Relation Terhadap Kinerja Karyawan Serta Pembentukan Lingkungan Kerja Yang Positif dan Produktif - Elok Kemala Motik; Risma Yanti; Nova Nazwa; Intan Widiyanti; April Laksana (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This study aims to analyze the influence of effective communication in human relations on employee performance and the formation of a positive and productive work environment. The methodology used in this study is a literature study by collecting references from several previous studies. The results of this study show that effective communication has an important role in employee performance. Effective communication can improve performance, create a positive and productive work environment and increase employee productivity. The conclusion of this study is that effective communication has a significant impact on employee performance and the formation of a positive and productive work environment. The implication of these findings is that managers need to develop effective communication strategies and create a workplace culture that supports open and transparent communication.